The Effect and Mechanism of Calcium Ions Concentration on Biofouling Grown in Treated Sewage Source Heat Pump Systems - Chang Siyuan; Fang Yuqing; Shi Lin (Zhileng xuebao)
Treated sewage source heat pump systems could reuse the large amount of wasted heat in the city sewage to refrigerate and heat the buildings. However, biofouling, which is the key problem in treated sewage heat pump systems, decreases the system efficiency and security. Ca2+, which is an important inorganic ion for bacteria metabolism, has a significant influence on biofouling formation. In this study, the effect and mechanism of calcium ions concentration on biofouling growth were investigated under flowing conditions. Model sewage was prepared, with the Ca2+ concentration ranging from 100 mg/L to 450 mg/L, and a rotating coupon device was used for biofouling formation. The total weight, dry weight and organic weight of biofouling grown under different Ca2+ concentrations were measured, the moisture content of the biofouling was calculated, and the microstructure of the biofouling was viewed. The results indicated that biofouling grown under higher Ca2+ concentrations have a more heterogeneous and porous structure, thus the moisture content and the total mass of the biofouling were increased. The results of this study could be used for predicting the biofouling formation under different operation conditions and improving the performance of treated sewage source heat pump systems.